Success Rates Of Dental Implants Among Saudi Patients With Diabetes Or Osteoporosis (The Review of Diabetic Studies, 2024)
Background: Dental implant therapy in patients with systemic conditions, such as diabetes mellitus and osteoporosis, remains a clinical challenge due to potential impacts on osseointegration and peri-implant health. This study aimed to evaluate implant survival and clinical success in medically complex patients and to assess the influence of disease control on treatment outcomes.Methods: A total of 300 patients (180 females, 120 males; mean age 54.3 ± 10.7 years) with diabetes mellitus (n = 170) or osteoporosis (n = 130) received 450 dental implants. Clinical and radiographic follow-up assessed implant survival, success according to Albrektsson criteria, and marginal bone loss. Statistical analyses included logistic regression and Kaplan–Meier survival analysis to identify predictors of implant outcomes.Results: Overall implant survival was 96.7%, with a clinical success rate of 94%. In diabetic patients, survival and success rates were 96.4% and 93.2%, respectively, with well-controlled diabetes associated with the highest success (97%). Poor glycemic control significantly increased the risk of implant complications (OR = 3.5; p < 0.001). Osteoporotic patients achieved 97% survival and 94.5% success, with T-score moderately influencing marginal bone loss (p = 0.03) but not overall survival. Smoking emerged as an independent risk factor for complications (OR = 2.1; p = 0.01). Comparative analysis revealed no significant difference in overall implant survival between systemic disease groups (p = 0.48).Conclusions: Dental implants demonstrate high survival and clinical success in patients with diabetes mellitus or osteoporosis, provided systemic conditions are appropriately managed. Glycemic control in diabetes and bone quality in osteoporosis are key determinants of outcomes, while modifiable factors such as smoking remain important risk considerations. These findings support the predictability of implant therapy in medically complex populations when individualized treatment planning and risk management are implemented.